Quality by Design Based RP-HPLC Method Development and Validation for the Simultaneous Estimation of Atazanavir and Ritonavir in Pure and Pharmaceutical Dosage Form - Swati Sanjay, Shinde; Mittal, Abhilasha; Santosh A, Waghmare (Journal of Neonatal Surgery, 2025)
The method Development and validation for Simultaneous Estimation of Atazanavir and Ritonavir in pure and pharmaceutical dosage form is done by using RP-HPLC (Jasco-Series 2000) based on Quality by Design technique. Chromatographic separations were carried out on Analytical column: C18 column Waters X Bridge (4.6× 250mm id. particle size 5µm), UV detection: 247nm. Injection volume: 20 µL, Flow rate: 1.00 mL min -1, Temperature: Ambient, Run time: 10 min. 2 Level Factorial Design gave 4 runs at different pH and Mobile phase proportion. A mixture of acetonitrile, potassium dihydrogen phosphate (pH-3, KH2PO4) and methanol (90:10) was used as the mobile phase. The pH of the buffer solution was adjusted by phosphoric acid (H3PO4) and triethylamine (TEA). The wavelength of 247nm was used as detection at which both drugs gave good response.